2023
DOI: 10.1021/acs.est.2c07611
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endocrine-Disrupting Chemicals with All-Cause and Cause-Specific Mortality in the U.S.: A Prospective Cohort Study

Abstract: Wide exposure to endocrine-disrupting chemicals (EDCs) poses a great risk on human health. However, few large-scale cohort studies have comprehensively estimated the association between EDCs exposure and mortality risk. This study aimed to investigate the association of urinary EDCs exposure with mortality risk and quantify attributable mortality and economic loss. Multivariable Cox proportional hazards regression models were performed to investigate the association of 38 representative EDCs exposure with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Finally, in this review we identified one paper assessing the relationship between EDCs and N-EDCs, such as PEs, and human mortality in a prospective cohort study. The study found a positive correlation between genistein and all-cause mortality, while enterolactone showed an inverse correlation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in this review we identified one paper assessing the relationship between EDCs and N-EDCs, such as PEs, and human mortality in a prospective cohort study. The study found a positive correlation between genistein and all-cause mortality, while enterolactone showed an inverse correlation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings additionally demonstrate that there exists a distinct chemical specificity between environmental substances and the risk of mortality. Previous research in the field of mortality risk among the overall populace has indicated a strong correlation between the element cadmium and tumor fatality ( 18 , 19 ). It is suggested that PCDD may also have similar risks.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites of the investigated EDCs were used as biomarkers of exposure (Table ). The biomarkers were selected based on (1) the response relationship between each parent compound and the biomarker and (2) the detection frequencies among reported populations, which exceeded 50%. For the detection of OFR metabolites (mOFRs), 100 μL of 200 ng/mL mixed internal standards (IS) (i.e., d 8-BBOEP, d 8-BCEP, d 12-BCIPP, d 10-BDCIPP, d 18-DBP, d 14-DoCP, d 14-DpCP, and d 10-DPHP) and 12 μL of formic acid were added to 2 mL of urine. After cartridge activation with 2 mL of 5% NH 4 OH in methanol and 3 mL of 0.6% formic acid in water, solid-phase extraction was conducted using CNW polysery PWAX cartridges.…”
Section: Methodsmentioning
confidence: 99%